A novel shaped ultrawideband fractal antenna for medical purposes. (February 2023) - Sediq, Hiwa Taha; Nourinia, Javad; Ghobadi, Changiz; Mohammadi, Bahman
Abstract: An ultra-wideband (UWB) fractal antenna based on a new epsilon-shaped geometry is described in this paper for microwave applications in the medical field. The antenna geometry is designed by combining four epsilon shapes and three pairs of straight-line conductors. The new configuration has an impedance bandwidth ranging from 2.58 to 20.95 GHz. The size of the designed antenna is 26 mm × 22 mm ( 0.22 λ L × 0.19 λ L ) with a wavelength of 116.3 mm. For a novel design technique, a reconfigurable patch antenna is proposed for 3.6 GHz (Wi-max), 5.4 GHz (WLAN), 3.1–10.6 GHz (UWB), and all applications operating in the X band(8–12 GHz) and Ku-band(12–18 GHz). ADS software is applied to configure and validate a comprehensive equivalent circuit model, and CST software is used to perform the full-wave analysis of the proposed antenna. A prototype of the suggested antenna is fabricated on a substrate of FR4 with a height of 1.6 mm to confirm the entire wave investigation and the theoretical solution outcomes of the circuit. It is proved that the comparative outcomes of the measurement and simulation have a good agreement. The proposed antenna also provides a high realized gain magnitude of 7.21 dB at an operational frequency of 20.95 GHz.